Synthesis, characterization and biomedical application of silver nanoparticles - Naganthran, Ashwini; Verasoundarapandian, Gayathiri; Khalid, Farah Eryssa; Masarudin, Mas Jaffri; Zulkharnain, Azham; Mohammad Nawawi, Norazah; Karim, Murni; Che Abdullah, Che Azurahanim; Ahmad, Siti Aqlima (Multidisciplinary Digital Publishing Institute, 2022)
Silver nanoparticles (AgNPs) have been employed in various fields of biotechnology due to their proven properties as an antibacterial, antiviral and antifungal agent. AgNPs are generally synthesized through chemical, physical and biological approaches involving a myriad of methods. As each approach confers unique advantages and challenges, a trends analysis of literature for the AgNPs synthesis using different types of synthesis were also reviewed through a bibliometric approach. A sum of 10,278 publications were analyzed on the annual numbers of publication relating to AgNPs and biological, chemical or physical synthesis from 2010 to 2020 using Microsoft Excel applied to the Scopus publication database. Furthermore, another bibliometric clustering and mapping software were used to study the occurrences of author keywords on the biomedical applications of biosynthesized AgNPs and a total collection of 224 documents were found, sourced from articles, reviews, book chapters, conference papers and reviews. AgNPs provides an excellent, dependable, and effective solution for seven major concerns: as antibacterial, antiviral, anticancer, bone healing, bone cement, dental applications and wound healing. In recent years, AgNPs have been employed in biomedical sector due to their antibacterial, antiviral and anticancer properties. This review discussed on the types of synthesis, how AgNPs are characterized and their applications in biomedical field.